Development of a Remote Version of the Graded Redefined Assessment of Strength, Sensation, and Prehension (GRASSP): Validity and Reliability. (February 2023) - Voss, Stephanie; Adighibe, Andrea; Sanders, Emily; Aaby, David; Kravitt, Rachel; Clark, Gina; Breen, Kelly; Barry, Alexander; Forrest, Gail F.; Kirshblum, Steve C.; Perez, Monica A.; Kalsi-Ryan, Sukhvinder; et al.
Background: The Graded Redefined Assessment of Strength, Sensation, and Prehension (GRASSP V1.0) was developed in 2010 as a 3-domain assessment for upper extremity function after tetraplegia (domains: Strength, Sensibility, and Prehension). A remote version (rGRASSP) was created in response to the growing needs of the field of Telemedicine. Objective: The purpose of this study was to assess the psychometric properties of rGRASSP, establishing concurrent validity and inter-rater reliability. Methods: Individuals with tetraplegia (n = 61) completed 2 visits: 1 in-person and 1 remote. The first visit was completed in-person to administer the GRASSP, and the second visit was conducted remotely to administer the rGRASSP. The rGRASSP was scored both by the administrator of the rGRASSP (Examiner 1), and a second assessor (Examiner 2) to establish inter-rater reliability. Agreement between the in-person and remote GRASSP evaluations was assessed using the intraclass correlation coefficient (ICC) and Bland–Altman agreement plots. Results: The remote GRASSP demonstrated excellent concurrent validity with the GRASSP (left hand intraclass correlation coefficient (ICC) = .96, right ICC = .96). Concurrent validity for the domains was excellent for strength (left ICC = .96, right ICC = .95), prehension ability (left ICC = .94, right ICC = .95), and prehension performance (left ICC = .92, right ICC = .93), and moderate for sensibility (left ICC = .59, right ICC = .68). Inter-rater reliability for rGRASSP total score was high (ICC = .99), and remained high for all 4 domains. Bland–Altman plots and limits of agreements support these findings. Conclusions: The rGRASSP shows strong concurrent validity and inter-rater reliability, providing a psychometrically sound remote assessment for the upper extremity in individuals with tetraplegia.